A reconfiguração da temporalidade da rádio na era da Internet - Reis, Ana Isabel (2011)
The radio reflects our time and how we relate to time. On the internet radio launches a new temporality. Of all the defining characteristics the time is probably the most profoundly changed, which also reflects how much has changed the way we live the every day life: accelerated and in pause; eternal and fleeting, episodic and continuous. Times have changed and the time of radio and their listeners have followed that trend by establishing not only a time, as before, but multiple times, usually as many as the listeners and their moods.In this reflection we aim to address the changes that technology and its appropriation by the listener operated in the temporality of traditional radio, the webradio, and the listener.